Pengaruh Pemahaman Akuntansi Perpajakan terhadap Kepatuhan Pajak di Kalangan UMKM Kota Mataram - Putri, Dina Amalya; Feriansyah (Jurnal Aplikasi Perpajakan, 2025)
This study aims to analyze the influence of tax accounting comprehension on tax compliance among Micro, Small, and Medium Enterprises (MSMEs) in Mataram City. The research employed a quantitative associative approach with data collected through structured questionnaires. A total of 100 active MSME respondents were selected using purposive sampling. The data were analyzed using simple linear regression. The results indicate that tax accounting comprehension has a positive and significant effect on tax compliance, with a regression coefficient of 0.651 and a determination coefficient (R²) of 0.487. These findings support the Theory of Planned Behavior and Deterrence Theory, highlighting the importance of tax literacy in shaping compliant behavior. Therefore, enhancing MSME actors' understanding of tax and accounting is a key factor in improving sustainable tax compliance.